Proceedings of the 5th ACM SIGCHI Symposium on Engineering Interactive Computing Systems 2013
DOI: 10.1145/2494603.2480311
|View full text |Cite
|
Sign up to set email alerts
|

Formal description of multi-touch interactions

Abstract: The widespread use of multi-touch devices and the large amount of research that has been carried out around them has made this technology mature in a very short amount of time. This makes it possible to consider multi-touch interactions in the context of safety critical systems. Indeed, beyond this technical aspect, multi-touch interactions present significant benefits such as input-output integration, reduction of physical space, sophisticated multi-modal interaction … However, interactive cockpits belonging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Nam et al showed how to use Coloured Petri Nets (CPN) to achieve hand (data glove) gesture modeling and recognition [14], using Hidden Markov Models (HMM) to recognize gesture features that are then fed to a Petri Net. Petri Nets have been shown to be applicable in event-driven system [15], which is another reason we are interested in them to model input devices. While our approach is based on high-level Petri Nets, Spano et al [16,17] showed how to use Non-Autonomous Petri Nets [18], low-level Petri Nets, for multi-touch interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nam et al showed how to use Coloured Petri Nets (CPN) to achieve hand (data glove) gesture modeling and recognition [14], using Hidden Markov Models (HMM) to recognize gesture features that are then fed to a Petri Net. Petri Nets have been shown to be applicable in event-driven system [15], which is another reason we are interested in them to model input devices. While our approach is based on high-level Petri Nets, Spano et al [16,17] showed how to use Non-Autonomous Petri Nets [18], low-level Petri Nets, for multi-touch interaction.…”
Section: Introductionmentioning
confidence: 99%
“…While our approach is based on high-level Petri Nets, Spano et al [16,17] showed how to use Non-Autonomous Petri Nets [18], low-level Petri Nets, for multi-touch interaction. Also, Hamon et al [15] expanded on Spano's work, providing more detail to the implementation of Petri Nets for multi-touch interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Coloured Petri Nets (CPN) to achieve hand (data glove) gesture modeling and recognition [151], using HMM to recognize gesture features that are then fed to a Petri Net (PN). PNs have been shown to be applicable in event-driven systems [75], which is another reason they are interesting to use for modeling modern input devices. Spano et al [198,199] showed how to use Non-Autonomous PNs [35] (low-level PNs), for multi-touch interaction.…”
Section: Modelingmentioning
confidence: 99%
“…Spano et al [198,199] showed how to use Non-Autonomous PNs [35] (low-level PNs), for multi-touch interaction. Also, Hamon et al [75] expanded on Spano's work, providing more detail to the implementation of PNs for multi-touch interactions.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation